Spatio-temporal impacts of a utility's efficiency portfolio on the distribution grid. (1st December 2020) - Granderson, Jessica; Fernandes, Samuel; Touzani, Samir; Lee, Chih-Cheng; Crowe, Eliot; Sheridan, Margaret
Abstract: Energy Efficiency has historically focused on delivering savings to offset growth in energy supply. Today's growing emphasis on decarbonization of the energy supply is driving renewables adoption and increased interest in electrification. As a result, energy efficiency is being assessed not just in its ability to offset load growth, but also for its ability to alleviate location-specific constraints on transmission and distribution infrastructure. This work demonstrates that advanced measurement and verification modeling techniques can be used to estimate the spatio-temporal grid impact of a portfolio of energy efficiency programs. It extends measurement-based methods to an entire Demand Side Management portfolio and uses a single model to predict annual as well as seasonal building energy use with near-zero bias. In addition, new metrics are introduced to assess grid level impacts of energy efficiency. The results show that the efficiency program portfolio delivers savings of over 12% at the territory-wide proxy level, with substation and feeder level savings ranging from 0.4% to 26%, and −5%-42% respectively. These savings impacted 1.0%–1.4% of the energy used at these locations in the grid. This work provides a methodology with potential to connect efficiency with distribution planning, carrying implications for non-wires alternatives and targeted delivery of efficiency programs. Highlights: Meter-based modeling was used to assess efficiency program impacts on the grid. Advanced metering infrastructure data enabled spatio-temporal disaggregation. Savings at analyzed substations and feeders ranged 0%–42%. These savings impacted of 1.0%–1.4% of the energy used in the distribution grid. Hourly results for each season surfaced the savings shapes and timing of the peak.